Deviant Peer Association as a Risk Factor for Firearm Carrying Among Justice-Involved Youth: The Mediating Roles of Exposure to Violence and Moral Disengagement - Wojciechowski, Thomas W. (Crime & delinquency, 2025)
Deviant peer association has been identified as a risk factor for firearm carrying among adolescents. However, there remains a dearth of research examining mechanisms explaining this relationship. This study addressed this gap in the literature by examining victimization and moral disengagement as mediators of the relationship between deviant peer association and firearm carrying risk among a sample of justice-involved youth. The first four waves of data from the Pathways to Desistance study were analyzed. Generalized structural equation modeling was used to test for direct and indirect effects. Results indicated that deviant peer association was significantly associated with increased log-odds of carrying a firearm. While neither victimization nor moral disengagement significantly mediated this relationship, the combined mediation effect was significant.